RAPID ANALYTICAL METHOD FOR ASSAY DETERMINATION FOR PROCHLORPERAZINE EDISYLATE DRUG SUBSTANCES BY ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY - Mule, Kishorkumar L. (International Journal of Current Pharmaceutical Research, 2017)
Objective: To develop and validate new, simple and rapid assay method for Prochlorperazine edisylate drug substance by UPLC as per ICH guidelines. Methods: Ultra performance liquid chromatographic method was developed, optimized and validated on Acquity UPLC by using Acquity BDH300 C4 (100 x 2.1 mm) 1.7µ column. 3.85g ammonium acetate in 1000 ml of water add 0.5 ml trifluoroacetic acid and 1 ml triethylamine (Mobile phase A): 0.5 ml trifluoroacetic acid in 1000 ml acetonitrile mobile phase (Mobile phase B) with gradient program. Detector wavelength 254 nm and column temperature 30 °C. Results: Linearity study was carried out for prochlorperazine edisylate, linearity was calculated from 80 % level to 120% with respect to specification level. The correlation coefficient (r) = 0.999 was proved that the method is robust. The resolution between known impurities and Prochlorperazine edisylate found more than 2.5, it was evident from specificity test that Prochlorperazine edisylate peak are well separated from its related impurities, hence the method is specific. Prochlorperazine edisylate sample solution and mobile phase were found to be stable for at least 3 d. Conclusion: A new, simple and rapid method has been developed and validated for assay determination of prochlorperazine edisylate in drug substance by Ultra Performance Liquid Chromatography (UPLC). The analytical method was developed and validated as per ICH guidelines. The developed method can be used for the fast assay determination of prochlorperazine edisylate drug substances in research laboratories and in the pharmaceutical industry.